PIPK1b regulates integrin endocytosis for focal adhesion disassembly by modulating the recruitment of the endocytic machinery to focal adhesions - Beisekenova, S.; Ospanova, B.; Kabdullayeva, T.; Chao, W. T.; Kunz, J. (Nazarbayev University, 2014)
Cell migration and tissue invasion during tumor metastasis require the regulated disassembly of focal adhesions, but the underlying mechanisms remain poorly defined. We previously showed that the turnover of focal adhesions occurs through odpha5Peta1 integrin endocytosis from focal adhesions (1). We further discovered that only integrins in their active conformation are internalized during focal adhesion disassembly and we set out to define the molecular machinery responsible for integrin transport (1,2). These studies revealed that the pathway required for the trafficking of active integrins involves different components than the pathway required for the trafficking of inactive integrins (1,2). Significantly, only by inhibiting the endocytosis of activated integrins was cell migration inhibited (2). Hence, the further identification of key components of the focal adhesion disassembly pathway is likely to expose novel avenues to inhibit tumor cell invasion and metastasis.
Keywords: PIPK1b; alpha5beta1; endocytosis; phosphatidylinositol; 4-phosphate; phosphatidylinositol-4; 5-kinase beta PIPK1P; via synthesis of PI4,5P2